The Impact of Economic Forces on Resource Use, State of Conservation, and Productivity of Rangelands in Northeastern Balochistan - Buzdar, Nek (Hanken, 2014)
In Musakhel and Barkhan districts of Balochistan and along the western slopes of the main Sulaiman mountain range, Baloch tribes raise animals, mainly sheep and goat, on rangelands that are commonly owned. This paper looks into the impact of economic forces such as income, prices, interest rates, and taxes on an individual animal raiser’s behavior towards resource use and productivity. An individual animal raiser’s behavior towards resource use expressed in number of animals raised per unit of rangeland/stocking rates/use rates, directly impacts rangeland productivity or carrying capacity because the rangelands in Balochistan are generally overgrazed. Under such overgrazed conditions an increase in stocking/use rates leads to a decrease in range carrying capacity or productivity and a decrease in stocking/use rates leads to an increase in carrying capacity or productivity of the rangelands. The paper analyzes changes in economic forces that lead to changes in animal raiser behavior and changes in animal raiser behavior that lead to changes in range carrying capacity and productivity.